EVALUATION OF THE MECHANICAL BEHAVIOR OF SOIL-CEMENT BRICKS WITH THE ADDITION OF RUBBER TIRE WASTE (REMUNOM, 2026)
This study evaluates the technical and environmental feasibility of using washed massará as a replacement for conventional sand in concrete production. Mineralogical characterization by X-ray diffraction (XRD) and X-ray fluorescence (XRF) revealed that both materials are predominantly siliceous, with quartz as the main phase. The conventional sand presented 91.36% SiO₂, whereas massará, despite its lower silica content (73.71%), exhibited a more complex mineralogy, including the presence of kaolinite (16.62% Al₂O₃) and feldspars, also supported by K₂O contents and loss on ignition. From a physical standpoint, a significant granulometric difference was observed: massará showed a fineness modulus (FM) of 2.61, being classified as a medium sand with a tendency toward coarser material, approaching the behavior of coarse sand, while the conventional sand presented an FM of 1.93, being classified as fine sand. This higher granulometry of massará favors better particle packing and lower void content, whereas fine sand increases specific surface area and water demand. Mechanical tests demonstrated the superior performance of massará, which reached 43.48 MPa at 91 days, exceeding the reference concrete by 32%. Statistical analysis (ANOVA and Tukey) confirmed that massará achieves, at 7 days, a compressive strength equivalent to that of conventional sand at 28 days (p < 0.001). It is concluded that the improved granulometric packing of massará, combined with its mineralogical composition, enhances the strength and durability of concrete, representing a sustainable alternative to sand extraction from riverbeds.